2021
DOI: 10.1093/sleep/zsab081
|View full text |Cite
|
Sign up to set email alerts
|

Brain reactivity to humorous films is affected by insomnia

Abstract: Study objectives Emotional reactivity to negative stimuli has been investigated in insomnia, but little is known about emotional reactivity to positive stimuli and its neural representation. Methods We used 3T fMRI to determine neural reactivity during the presentation of standardized short, 10-40-s, humorous films in insomnia patients (n=20, 18 females, aged 27.7 +/- 8.6 years) and age-matched individuals without insomnia (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Patients with insomnia show attentional bias when presented with sleep‐related emotional stimuli (Barclay & Ellis, 2013; MacMahon et al, 2006; Lundh et al, 1997; for review, see Harris et al, 2015). Brain regions typically active when emotional stimuli are presented, such as the amygdala (Baglioni et al, 2014) and the brain reward network (Sanz‐Arigita et al, 2021), show increased activity and connectivity in patients with insomnia compared with controls. These findings may, though based on a limited number of studies, offer neural support for increases of selective attention of sleep‐related information, in the context of the opposite pattern of hypoactivity in prefrontal brain regions when presented with cognitive tasks.…”
Section: Cognitive and Emotional Processing Factors Of Insomnia And C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with insomnia show attentional bias when presented with sleep‐related emotional stimuli (Barclay & Ellis, 2013; MacMahon et al, 2006; Lundh et al, 1997; for review, see Harris et al, 2015). Brain regions typically active when emotional stimuli are presented, such as the amygdala (Baglioni et al, 2014) and the brain reward network (Sanz‐Arigita et al, 2021), show increased activity and connectivity in patients with insomnia compared with controls. These findings may, though based on a limited number of studies, offer neural support for increases of selective attention of sleep‐related information, in the context of the opposite pattern of hypoactivity in prefrontal brain regions when presented with cognitive tasks.…”
Section: Cognitive and Emotional Processing Factors Of Insomnia And C...mentioning
confidence: 99%
“…and the brain reward network(Sanz-Arigita et al, 2021), show increased activity and connectivity in patients with insomnia compared with controls. These findings may, though based on a limited number of studies, offer neural support for increases of selective attention of sleep-related information, in the context of the opposite pattern of hypoactivity in prefrontal brain regions when presented with cognitive tasks.Effective treatment can be achieved by cognitive restructuring, which focuses on increasing the patient's awareness of the ineffectiveness of dramatising thoughts and dysfunctional beliefs about lack of sleep and its consequences but also, importantly, on their aggravating influence on insomnia.…”
mentioning
confidence: 94%
“…The role of the dorsal striatum (DS; i.e., dorsal caudate nucleus and putamen) in humor processing has generally been overlooked. Although activations of the left putamen ( Iwase et al, 2002 ; Filik et al, 2019 ; Sanz-Arigita et al, 2021 ), the right putamen ( Goldin et al, 2005 ; Neely et al, 2012 ; Shibata et al, 2014 ), the left caudate ( Sanz-Arigita et al, 2021 ), and the right caudate ( Goldin et al, 2005 ; Osaka et al, 2014 ; Sanz-Arigita et al, 2021 ) have been identified in studies of humor processing, most authors do not put importance on these findings or discuss their implications. Filik et al (2019) were the lone authors to discuss the role of the putamen in language processing and how this could contribute to humor comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of neuroimaging techniques enables scientists to substantially investigate brain regions involved in emotion regulation. Limbic systems (e.g., insula, cingulate gyrus, and hippocampus), prefrontal cortex, and temporal cortex are among the most frequently researched areas (Cheng et al, 2018;Killgore, 2013;Motomura et al, 2017;Sanz-Arigita et al, 2021). The amygdala, for instance, is well documented for its role in processing aversive information (Tamm et al, 2020;Yoo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%